Association between frailty status and osteomyelitis: A nested case-control study - Can Guo; Xukun Luo; Zijin Tang; Jian Zhou; Tang Liu (PLoS ONE, 2026)
Background Although frailty has been recognized as a predictor of various adverse outcomes in older adults, the association between physical pre-frailty or frailty and the risk of osteomyelitis remains unclear. Methods In this nested case-control study, data from 466,918 eligible participants recruited into the UK Biobank between 2006 and 2010 were used. Incident osteomyelitis cases were identified through linked electronic health records up to 19 December 2022 and matched to controls at a 1:5 ratio by age, sex, and assessment center from the baseline population meeting the eligibility criteria. Frailty status was assessed at baseline using a five-item phenotype adapted from the Fried criteria and categorized as non-frail, pre-frail, or frail. Conditional logistic regression was used to evaluate the association between frailty status and osteomyelitis after adjustment for socioeconomic factors, lifestyle behaviors, medication use, and clinical risk factors. Results Compared with non-frail individuals, participants with physical pre-frailty had a significantly higher odds of osteomyelitis (OR = 1.38; 95% CI: 1.16–1.64), with the odds further increasing among those with physical frailty (OR = 2.79; 95% CI: 2.05–3.81), demonstrating a clear dose–response relationship (P-trend <0.001). These associations between physical frailty status and osteomyelitis remained robust across subgroups defined by potential risk factors. Conclusions Physical pre-frailty and frailty were associated with higher odds of osteomyelitis, with the odds increasing across frailty categories.